2022
DOI: 10.1111/1467-8551.12664
|View full text |Cite
|
Sign up to set email alerts
|

Responsible Investment and Stock Market Shocks: Short‐Term Insurance without Persistence

Abstract: We investigate the differential effect of the COVID-19 shock on the share prices of firms with different levels of ESG (environmental, social and governance) scores. Thereby, we analyse whether and to what extent higher ESG ratings provided insurance for investors in the stocks of those firms during this shock. We focus our analysis on the European market, in which ESG investment plays a particularly important role. Using a broad sample of listed firms, we provide mixed evidence. On the one hand, we show that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 59 publications
0
5
0
Order By: Relevance
“…However, when it comes to FP, no discernible difference in impact is observed between sustainable and non-sustainable firms. The effectiveness of ESG as a crisis-mitigation strategy is further supported by studies conducted by Engelhardt et al (2021), Khoury et al (2022), Eisenkopf et al (2022) and Li et al (2022). Conversely, Bae et al (2021) and Bodhanwala and Bodhanwala (2023) suggest an insignificant impact of ESG on stock returns, indicating that the role of ESG in cushioning risks may not always hold.…”
Section: Review Of Literaturementioning
confidence: 87%
“…However, when it comes to FP, no discernible difference in impact is observed between sustainable and non-sustainable firms. The effectiveness of ESG as a crisis-mitigation strategy is further supported by studies conducted by Engelhardt et al (2021), Khoury et al (2022), Eisenkopf et al (2022) and Li et al (2022). Conversely, Bae et al (2021) and Bodhanwala and Bodhanwala (2023) suggest an insignificant impact of ESG on stock returns, indicating that the role of ESG in cushioning risks may not always hold.…”
Section: Review Of Literaturementioning
confidence: 87%
“…These qualities have become especially relevant during the COVID-19 pandemic, as investors have engaged in a documented shift toward sustainable investments. However, more recent evidence supports the idea that ESG stocks provide limited insurance and act as a temporary risk-mitigating device in severe crises (Eisenkopf et al, 2022). Consequently, there is still a question as to whether investors can use selective ESG investing to protect their wealth during economic downturns and/or diversify/hedge their portfolios and through what types of ESG investments.…”
Section: Discussionmentioning
confidence: 99%
“…Demers et al (2021), observing a sample of US firms, presented robust evidence that Refinitiv‐Eikon‐MSCI ESG ratings were not a share price resilience factor during the COVID‐19 pandemic, concluding that ESG ratings did not immunize stocks during the crisis whereas investments in intangible assets did. Eisenkopf et al (2022) observed the effect of the COVID‐19 shock on the share prices of firms in the European market with different levels of ESG ratings and found mixed evidence that investing in higher ESG‐rated firms could provide insurance for investors, showing this limited effect fading quickly. Basnet et al (2022) focused on another crisis, the 2022 Russian invasion of Ukraine, and investigated whether ESG scores influence a firm's choice to stay in or leave the Russian market, with consequent stock market reaction.…”
Section: Thematic and Content Analysismentioning
confidence: 99%
“…Eisenkopf et al (2022) observed the effect of the COVID-19 shock on the share prices of firms in the European market with different levels of ESG ratings and found mixed evidence that investing in higher ESG-rated firms could provide insurance for investors, showing this limited effect fading quickly Basnet et al (2022). focused on another crisis, the 2022 Russian invasion of Ukraine, and investigated whether ESG scores influence a firm's choice to stay in or leave the Russian market, with consequent stock market reaction.…”
mentioning
confidence: 99%